Fault Attack on the Authenticated Cipher ACORN v2. (2nd October 2017) - Zhang, Xiaojuan; Feng, Xiutao; Lin, Dongdai
Abstract : Fault attack is an efficient cryptanalysis method against cipher implementations and has attracted a lot of attention in recent public cryptographic literatures. In this work we introduce a fault attack on the CAESAR candidate ACORN v2. Our attack is done under the assumption of random fault injection into an initial state of ACORN v2 and contains two main steps: fault locating and equation solving. At the first step, we first present a fundamental fault locating method, which uses 99-bit output keystream to determine the fault injected location with probability 97.08 % . And then several improvements are provided, which can further increase the probability of fault locating to almost 1. As for the system of equations retrieved at the first step, we give two solving methods at the second step, that is, linearization and guess-and-determine. The time complexity of our attack is not larger than c · 2 179.19 - 1.76 N at worst, where N is the number of fault injections such that 31 ≤ N ≤ 88 and c is the time complexity of solving linear equations. Our attack provides some insights into the diffusion ability of such compact stream ciphers.